Enhancing Maternal Knowledge and Practices in Complementary Feeding through Emotional Demonstration Methods - Ani Intiyati; Imam Sarwo Edi; Inne Soesanti; Juliana Christianingsih; Kusmini Suprihatin; Luluk Widarti (Amerta Nutrition)
Background: Complementary feeding is crucial for children's growth and development, especially between the ages of 6 to 24 months. Adequate nutritional intake during this period can prevent long-term health issues, such as stunting and obesity. However, many mothers struggle with providing appropriate complementary feeding due to a lack of knowledge and inappropriate feeding practices.